If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-12=4x+11
We simplify the equation to the form, which is simple to understand
6x-12=4x+11
We move all terms containing x to the left and all other terms to the right.
+6x-4x=+11+12
We simplify left and right side of the equation.
+2x=+23
We divide both sides of the equation by 2 to get x.
x=11.5
| 140-4x=5x | | (8x)= | | 140-4x=10x+17 | | x^2-15x+65=11565 | | factorisem^2+7m-10=0 | | 5cos(x+17)=4 | | m^2+7m-10=0 | | 5(3x+2)=-5 | | 5x-9=111-10x | | x(4-x)=x^2(7-x) | | 13210*X^2+6785600*x-5315460000=0 | | 4(3x-1)=56 | | (-7m^5n^5)(5mn^2)= | | (-4a^6b^6)(3ab^3)= | | x^2+5y=x^2 | | (b^9c^5)(b^7c)= | | 180-x^2+x-5=7x+5 | | x-5+x+5=39 | | (m^10n^3)(m^12n)= | | 32*x^5+1=0 | | 3(3*3)=-27 | | x+8+x^2-3x+3x-2+x+2=43 | | 17x+5=17x+5 | | 3x^2+4=999 | | 10=10x-x^2 | | k*k+5=9 | | 2(2x+2)+.5(x+1)=4(x+2) | | 8x-13+3x-5=180 | | 3/7(x+4)-2x+9/3=8/7(x+5)-5/3(x+3) | | x^5-2x=0 | | n^2-n-5200=0 | | x^2-mx+m^2-3=0 |